Micro-nano bicrystal tabular structure titanium carbonitride-based metal ceramic alloy and preparation method thereof
By adopting micro-nano double-crystalline carbonitride-based cermet alloy, the problem of insufficient strength and toughness under high impact is solved, and the high hardness, wear resistance and impact toughness of the material are significantly improved.
Patent Information
- Application Number
- CN202411756489.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
AI Technical Summary
Existing steel-junction cemented carbides have problems such as insufficient strength, insufficient toughness and low hardness under high impact, and are prone to deformation or fracture, affecting the structure and mechanical properties of the internal steel.
A micro-nano double-crystal plate-like structure titanium nitride-based metal cermetal alloy is used to form plate-like structure grains of micro-nano double-crystal carbon titanium nitride-based metal cermetal alloy with a certain thickness-diameter ratio through the formulation of hard phase powder, bonded phase powder and carbon nitrogen balance powder, and through the sintering process and the carbon content control, the carbon content is formed.
It significantly improves the impact toughness, hardness and wear resistance of the material, enhances the strength and hardness of the bonded phase matrix composite material, and improves the high-temperature mechanical properties and work hardening capabilities of the material.
Smart Images

Figure CN119571166A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of metal ceramic materials, and in particular to a titanium carbonitride-based metal ceramic alloy with a micro-nano twin crystal plate-like structure and a preparation method thereof. Background Art
[0002] In recent years, mining, metallurgy, cement and other industries have developed towards large-scale development. In the fields of building materials, thermal power generation, metallurgical mining and equipment manufacturing, the direct economic losses caused by product failure due to wear and tear at home and abroad have reached tens of billions or even more than 100 billion yuan each year. Among them, the wear-resistant materials that consume millions of tons of metal each year due to abrasive wear are still growing at a rate of 15% per year. TiC steel bonded carbide such as TM52 and steel TM60, although the strengthened steel alloy inside can play a certain role in enhancing toughness and impact resistance, still has insufficient strength and toughness under high impact, low hardness resulting in low wear resistance, and TM52 steel bonded carbide is still prone to deformation or fracture and other technical problems, which will further affect the actual organization and mechanical properties of the internal steel. Summary of the invention
[0003] In view of this, the present application provides a micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy and a preparation method thereof, aiming to improve the existing steel-bonded cemented carbide, which suffers from fracture and breakage due to insufficient toughness and greatly accelerated material wear rate due to low hardness when subjected to high impact.
[0004] The embodiment of the present application is implemented as follows: a micro-nano twinned plate-like structure titanium carbonitride-based metal-ceramic alloy, measured by mass percentage, comprises:
[0005] Hard phase powder: 30% to 80% first TiCN;
[0006] 1% to 10% second TiCN;
[0007] 0%~5% TiC;
[0008] Binder phase powder: 0% to 10% Ni;
[0009] 0%~10% Co;
[0010] 15%~65% Fe;
[0011] 1.5%~15% W-Fe;
[0012] Carbon-nitrogen balance powder: 0% to 1.5% carbon black;
[0013] The Fsss particle size of the first TiCN powder is greater than the Fsss particle size of the second TiCN powder.
[0014] Optionally, the metal ceramic alloy comprises, by mass percentage:
[0015] Hard phase powder: 30% to 80% first TiCN;
[0016] 1% to 10% second TiCN;
[0017] 0.1%~5% TiC;
[0018] Binder phase powder: 0.1% to 10% Ni;
[0019] 0.1%~10% Co;
[0020] 15%~65% Fe;
[0021] 1.5%~15% W-Fe;
[0022] Carbon-nitrogen balance powder: 0.1% to 1.5% carbon black.
[0023] Optionally, the first TiCN powder Fsss has a particle size greater than 1.8 μm and less than 6.5 μm; and / or
[0024] The second TiCN powder Fsss has a particle size of less than 1.0 μm; and / or
[0025] TiC powder Fsss particle size not greater than 3.5 microns; and / or
[0026] Ni powder Fsss particle size is not greater than 3.0 microns; and / or
[0027] Co powder Fsss particle size is not greater than 3.0 microns; and / or
[0028] The particle size of Fe powder Fsss is not greater than 100.0 microns; and / or
[0029] The particle size of the W-Fe powder Fsss is not greater than 100.0 microns; and / or
[0030] The particle size of the carbon black powder Fsss is less than 1.0 micron.
[0031] Optionally, the Fe powder is carbonyl iron powder or reduced iron powder; and / or
[0032] The mass percentage of W in W-Fe is 45% to 85%.
[0033] Optionally, .
[0034] Optionally, .
[0035] Accordingly, the present application also provides a method for preparing a micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy, the preparation method comprising:
[0036] Providing a mixed powder, the mixed powder comprising the hard phase powder, the binder phase powder and the carbon-nitrogen balance powder in the above-mentioned mass percentages;
[0037] Adding a dispersant and a molding agent to the mixed powder and mixing them evenly to obtain a prepared raw material;
[0038] ball-milling the prepared raw materials to obtain a mixed slurry;
[0039] Drying the mixed slurry and pressing to obtain a blank;
[0040] The blank is sintered to obtain a metal-ceramic alloy.
[0041] Optionally, the prepared raw materials are loaded into a grinding carbide or stainless steel ball mill of a ball mill, a solvent is added and ball milled to obtain a mixed slurry; and / or
[0042] The mixed slurry is dried and passed through an N-mesh filter or spray granulated. The powder after the filter or spray granulation is directly loaded into a mold and pressed into a blank.
[0043] Optionally, the dispersant comprises dodecylbenzenesulfonic acid, stearic acid or ethozone; and / or
[0044] The molding agent comprises rubber, paraffin or PEG; and / or
[0045] Solvents include gasoline, ethylene glycol, or hexane.
[0046] Optionally, the mass fraction of the dispersant in the total amount of the mixed powder is 0.3% to 0.8%; and / or
[0047] The mass fraction of the molding agent in the total amount of the mixed powder is 2.5% to 8%; and / or
[0048] The volume mass ratio of the solvent to the mixed powder is 250ml / Kg to 600ml / Kg; and / or
[0049] The ball mill is a rolling ball mill, the diameter of the carbide balls is 5.5 mm to 12 mm, the ball-to-material ratio is 3.5 to 8:1, the speed of the ball mill is 38 rpm to 80 rpm, and the ball milling time is 24 h to 80 h; and / or
[0050] N mesh is 40 mesh to 120 mesh; and / or
[0051] The pressing pressure is 150Mpa to 220Mpa; and / or
[0052] The pressure holding time is 2min to 20min.
[0053] Optionally, the blank is loaded into a sintering furnace and sequentially enters a heating and degreasing stage, a solid phase sintering stage, and a liquid phase sintering stage. After the liquid phase sintering is completed, the blank enters a furnace cooling stage, and then the metal ceramic alloy is taken out of the furnace;
[0054] The heating and degreasing stage is carried out according to the preheating, vacuuming, heating and insulation procedures, preheating to T1 temperature, insulation time t1; vacuuming to below 10Pa, heating to T2 temperature; heating speed is v1, insulation time t2 at T3 temperature;
[0055] During the solid phase sintering stage, the heating rate does not exceed v2, the heating temperature is increased from T3 to T4, and the temperature is kept for t3; the heating rate does not exceed v3, the heating temperature is increased from T4 to T5, and the temperature is kept for t4; the heating rate does not exceed v4, the heating temperature is increased from T5 to T6, and the temperature is kept for t5; the heating rate does not exceed v5, the heating temperature is increased from T6 to T7, and the temperature is kept for t6;
[0056] After the solid phase sintering stage is completed and the liquid phase sintering stage is entered, the temperature is increased to T8 at a heating rate of v6 and maintained at t7, while argon gas with a pressure of P is introduced.
[0057] Optionally, T1 is 180°C to 250°C; and / or
[0058] t1 is 60 min to 120 min; and / or
[0059] T2 is 380°C to 450°C; and / or
[0060] v1 is 3℃ / min~5℃ / min; and / or
[0061] T3 is 450°C to 600°C; and / or
[0062] t2 is 60 min to 180 min; and / or
[0063] v2 does not exceed 10℃ / min; and / or
[0064] T4 is 750°C to 850°C; and / or
[0065] t3 is 60 min to 180 min; and / or
[0066] v3 does not exceed 10℃ / min; and / or
[0067] T5 is 1000°C to 1100°C; and / or
[0068] t4 is 60 min to 180 min; and / or
[0069] v4 does not exceed 10℃ / min; and / or
[0070] T6 is 1200°C to 1250°C; and / or
[0071] t5 is 120 min to 300 min; and / or
[0072] v5 does not exceed 5℃ / min; and / or
[0073] T7 is 1300°C to 1350°C; and / or
[0074] t6 is 60 min to 120 min; and / or
[0075] v6 does not exceed 5℃ / min; and / or
[0076] T8 is 1350°C to 1500°C; and / or
[0077] t7 is 60 min to 300 min; and / or
[0078] P is 1MPa~5MPa.
[0079] Beneficial effects: The hard phase of the present invention has better interface bonding with the bonding phase and better impact toughness. TiC can effectively enhance the strength and hardness of the formed bonding phase-based composite material (TiM)CN. The W element can solid dissolve and strengthen the bonding phase, increase the hardness of the material and improve its wear resistance. The balanced carbon content can improve the hardness, strength and wear resistance of the steel. The submicron second TiCN is used to refine the grains, improve the toughness and increase the hardness of the hard particles, thereby significantly improving the toughness of the steel, improving the ability of work hardening, and significantly improving the wear resistance of the steel. BRIEF DESCRIPTION OF THE DRAWINGS
[0080] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0081] Figure 1 This is a flow chart of the method for preparing the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy of the present application;
[0082] Figure 2 This is a scanning electron microscope image of the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy obtained in Example 1 of the present application;
[0083] Figure 3 This is a scanning electron microscope image of the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy obtained in Example 2 of the present application;
[0084] Figure 4This is a scanning electron microscope image of the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy obtained in Example 3 of the present application;
[0085] Figure 5 This is a scanning electron microscope image of the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy obtained in Example 4 of the present application;
[0086] Figure 6 This is a scanning electron microscope image of the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy obtained in Example 5 of the present application;
[0087] Figure 7 This is a scanning electron microscope image of the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy obtained in Example 6 of the present application;
[0088] Figure 8 This is a scanning electron microscope image of the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy obtained in Example 7 of the present application.
[0089] Figure 8 In the figure, 1-plate-like micron crystals; 2-plate-like nanocrystals; 3-binding phase. DETAILED DESCRIPTION
[0090] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0091] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.
[0092] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0093] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, a~b (i.e. a and b), a~c, b~c or a~b~c, where a, b, c can be single or multiple, respectively.
[0094] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0095] The technical solution of this application is as follows:
[0096] In a first aspect, the present invention provides a micro-nano twinned plate-like structure titanium carbonitride-based metal-ceramic alloy, which comprises, by mass percentage:
[0097] Hard phase powder: 30% to 80% first TiCN;
[0098] 1% to 10% second TiCN;
[0099] 0%~5% TiC;
[0100] Binder phase powder: 0% to 10% Ni;
[0101] 0%~10% Co;
[0102] 15%~65% Fe;
[0103] 1.5%~15% W-Fe;
[0104] Carbon-nitrogen balance powder: 0% to 1.5% carbon black;
[0105] The Fsss particle size of the first TiCN powder is greater than the Fsss particle size of the second TiCN powder.
[0106] Further, in terms of mass percentage, the metal ceramic alloy comprises: a hard phase powder, the hard phase powder comprises: 30% to 80% of the first TiCN, preferably 40% to 70% of the first TiCN, more preferably 50% to 60% of the first TiCN; 1% to 10% of the second TiCN, preferably 2% to 8% of the second TiCN, more preferably 3% to 6% of the second TiCN, more preferably 4% to 5% of the second TiCN; 0% to 5% of TiC, preferably 0.1% to 5% of TiC, more preferably 1% to 4% of TiC, more preferably 2% to 3% of TiC; the metal ceramic alloy comprises: a bonding phase powder, the bonding phase powder comprises 0% to 10% of Ni, preferably 0.1% to 10% of Ni, more preferably 1% to 8% of Ni, more preferably 2% to 7% of Ni, more preferably 3% to 5% of Ni; 0% to 10% of Co, preferably 0.1% to 10% of Co, more preferably 1% to 8% of Co, more preferably 2% to 6% Co, more preferably 3% to 5% Co; 15% to 65% Fe, preferably 20% to 60% Fe, more preferably 25% to 55% Fe, more preferably 30% to 50% Fe, more preferably 35% to 45% Fe; 1.5% to 15% W-Fe, preferably 2% to 12% W-Fe, more preferably 4% to 10% W-Fe, more preferably 6% to 8% W-Fe; the metal ceramic alloy comprises: carbon-nitrogen balance powder, the carbon-nitrogen balance powder comprises 0% to 1.5% carbon black, preferably 0.1% to 1.5% carbon black; more preferably 0.5% to 1.2% carbon black; more preferably 0.8% to 1% carbon black.
[0107] The hard phase of the present invention has better interface bonding with the bonding phase and better impact toughness. TiC can effectively enhance the strength and hardness of the formed bonding phase-based composite material (TiM)CN. The W element can solid-dissolve and strengthen the bonding phase, increase the hardness of the material and improve its wear resistance. The balanced carbon content can improve the hardness, strength and wear resistance of the steel. The submicron second TiCN is used to refine the grains, improve the toughness and increase the hardness of the hard particles, thereby significantly improving the toughness of the steel, improving the ability of work hardening, and significantly improving the wear resistance of the steel.
[0108] The first TiCN, the second TiCN and the TiC-based steel-bonded hard alloy of the present invention have obvious advantages. From the perspective of cost, Ti is more abundant than W resources, and the preparation process of TiC powder is simple, resulting in its overall low price and low cost. From the perspective of product performance, the density of TiC is low, which is 4.8-6.5g / cm3, while the density of WC is 14.9-15.4g / cm 3, which is only about 1 / 3 to 1 / 2 of that of WC. The hardness of the first TiCN, the second TiCN and the TiC-based steel-bonded cemented carbide prepared therefrom is significantly higher than that of the WC-based steel-bonded cemented carbide, and they have better thermal stability and good high-temperature oxidation resistance, which has unique advantages for transport vehicles, aircraft and high-speed wear-resistant parts.
[0109] The present invention uses a first TiCN and a second TiCN with high hardness, TiC, a multi-component powder of a bonding matrix of N, Co, Fe and W-Fe, and a carbon-nitrogen balance powder carbon black to prepare a micro-nano twinned plate-shaped structure titanium carbonitride-based metal ceramic alloy. The present invention improves the ratio of the growth rate of the plate-shaped crystals through the control of the formula, sintering process and the amount of C, and forms plate-shaped structure grains of a micro-nano twinned titanium carbonitride-based metal ceramic alloy with a certain thickness-diameter ratio in the alloy. The presence of a large number of plate-shaped grains causes transgranular fracture during crack expansion, and the bridging of multi-component bonding phases such as Ni, Co, Fe, and W-Fe and crack deflection are greatly increased, thereby significantly improving toughness; the plate-shaped hard phase reduces its stacking fault energy, reduces the high-temperature creep rate of the alloy, and can improve its high-temperature mechanical properties. At the same time, the presence of a large number of plate-shaped grains also significantly increases the hardness of the material, so that the comprehensive mechanical properties of the material are significantly improved.
[0110] The present invention adopts iron-based powder as a bonding phase, and the sintering temperature is 50-100°C lower than that of cemented carbide, the tendency of grain growth is small, and the product has plastic deformation ability under high temperature conditions and excellent performance. From the perspective of subsequent machinability, the steel-bonded cemented carbide product can be subjected to various mechanical processing, heat treatment, forging and welding as required, and can obtain the strength, hardness, toughness and other performance required by the tool and die material, greatly improving the wear resistance of the mold, and is widely used in machinery, mining and metallurgy, construction, military, aerospace and other fields.
[0111] The micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy prepared by the present invention has low density, high hardness, wear resistance and other excellent physical and mechanical properties. Its preparation process is simple, easy to operate, the sintering cycle is highly controllable, the process cost is low, and it can be widely used in industrial production. It has a very high cost performance ratio and is an effective way to fill the gap between cemented carbide and steel. It can greatly save the use of precious metals such as W, Co, Ta and other strategic alloying elements, and effectively reduce the production cost of the alloy.
[0112] Furthermore, the metal ceramic alloy comprises, by mass percentage:
[0113] Hard phase powder: 30% to 80% first TiCN;
[0114] 1% to 10% second TiCN;
[0115] 0.1%~5% TiC;
[0116] Binder phase powder: 0.1% to 10% Ni;
[0117] 0.1%~10% Co;
[0118] 15%~65% Fe;
[0119] 1.5%~15% W-Fe;
[0120] Carbon-nitrogen balance powder: 0.1% to 1.5% carbon black;
[0121] The Fsss particle size of the first TiCN powder is greater than the Fsss particle size of the second TiCN powder.
[0122] Furthermore, the particle size Fsss of the first TiCN powder is greater than 1.8 microns and less than 6.5 microns. The particle size Fsss of the first TiCN powder can be, for example, 1.81 microns, 1.9 microns, 2 microns, 2.5 microns, 3 microns, 3.5 microns, 4 microns, 4.5 microns, 5 microns, 5.5 microns, 6 microns, 6.5 microns, etc. The powder particle size Fsss range is conducive to the combination with the second TiCN powder to improve the bending strength and wear resistance.
[0123] Furthermore, the second TiCN powder Fsss particle size is less than 1.0 micron, for example, it can be 0.01 micron, 0.02 micron, 0.04 micron, 0.06 micron, 0.08 micron, 0.1 micron, 0.2 micron, 0.4 micron, 0.6 micron, 0.8 micron, 0.9 micron, etc. The powder particle size Fsss range is conducive to the combination with the second TiCN powder to improve the bending strength and wear resistance.
[0124] Furthermore, the particle size Fsss of the TiC powder is not greater than 3.5 microns, and may be, for example, 0.01 microns, 0.02 microns, 0.04 microns, 0.06 microns, 0.08 microns, 0.1 microns, 0.2 microns, 0.4 microns, 0.6 microns, 0.8 microns, 1.0 microns, 1.2 microns, 1.3 microns, 1.5 microns, 1.8 microns, 2.0 microns, 2.2 microns, 2.4 microns, 2.5 microns, 2.6 microns, 2.8 microns, 3 microns, 3.1 microns, 3.2 microns, 3.3 microns, 3.4 microns, 3.5 microns, etc. Within the range of the powder particle size Fsss, it is beneficial to improve the hardness of the metal ceramic alloy and has good thermal stability.
[0125] Furthermore, the particle size of the Ni powder Fsss is not greater than 3.0 microns, for example, it can be 0.01 microns, 0.02 microns, 0.04 microns, 0.06 microns, 0.08 microns, 0.1 microns, 0.2 microns, 0.4 microns, 0.6 microns, 0.8 microns, 1.0 microns, 1.2 microns, 1.3 microns, 1.5 microns, 1.8 microns, 2.0 microns, 2.2 microns, 2.4 microns, 2.5 microns, 2.6 microns, 2.8 microns, 3 microns, etc. Within the range of the powder particle size Fsss, it has better bonding with the hard phase interface and better impact toughness.
[0126] Furthermore, the particle size of the Co powder Fsss is not greater than 3.0 microns, for example, it can be 0.01 microns, 0.02 microns, 0.04 microns, 0.06 microns, 0.08 microns, 0.1 microns, 0.2 microns, 0.4 microns, 0.6 microns, 0.8 microns, 1.0 microns, 1.2 microns, 1.3 microns, 1.5 microns, 1.8 microns, 2.0 microns, 2.2 microns, 2.4 microns, 2.5 microns, 2.6 microns, 2.8 microns, 3 microns, etc. Within the range of the powder particle size Fsss, it has better bonding with the hard phase interface and better impact toughness.
[0127] Furthermore, the particle size of the Fe powder Fsss is not greater than 100.0 microns, for example, it can be 0.01 micron, 0.02 micron, 0.04 micron, 0.06 micron, 0.08 micron, 0.1 micron, 0.2 micron, 0.4 micron, 0.6 micron, 0.8 micron, 1.0 micron, 8 micron, 10 micron, 15 micron, 20 micron, 25 micron, 30 micron, 35 micron, 40 micron, 45 micron, 50 micron, 55 micron, 60 micron, 65 micron, 70 micron, 75 micron, 80 micron, 85 micron, 90 micron, 95 micron, 98 micron, 99 micron, etc. Within the range of the powder particle size Fsss, it has better bonding with the hard phase interface and better impact toughness.
[0128] Furthermore, the W—Fe powder Fsss particle size is not greater than 100.0 microns, for example, it can be 0.01 microns, 0.02 microns, 0.04 microns, 0.06 microns, 0.08 microns, 0.1 microns, 0.2 microns, 0.4 microns, 0.6 microns, 0.8 microns, 1.0 microns, 8 microns, 10 microns, 15 microns, 20 microns, 25 microns, 30 microns, 35 microns, 40 microns, 45 microns, 50 microns, 55 microns, 60 microns, 65 microns, 70 microns, 75 microns, 80 microns, 85 microns, 90 microns, 95 microns, 98 microns, 99 microns, etc. Within the range of the powder particle size Fsss, it has better bonding with the hard phase interface and better impact toughness.
[0129] Furthermore, the particle size of the carbon black powder Fsss is less than 1.0 micron, for example, it can be 0.01 micron, 0.02 micron, 0.04 micron, 0.06 micron, 0.08 micron, 0.1 micron, 0.2 micron, 0.4 micron, 0.6 micron, 0.8 micron, 0.9 micron, etc. The powder particle size Fsss range is conducive to improving the hardness, strength and wear resistance of the metal ceramic alloy.
[0130] Furthermore, the Fe powder is carbonyl iron powder or reduced iron powder.
[0131] Furthermore, the mass percentage of W in W-Fe is 45% to 85%, for example, it can be 45%, 48%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, etc. Within the mass percentage range, it can dissolve and strengthen the bonding phase, increase the hardness of the material and improve its wear resistance.
[0132] Second, see Figure 1 The present application also provides a method for preparing a micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy, comprising:
[0133] S01. Providing a mixed powder, wherein the mixed powder comprises the hard phase powder, the binder phase powder and the carbon-nitrogen balance powder in the above-mentioned mass percentages;
[0134] S02, adding a dispersant and a molding agent to the mixed powder, and mixing them evenly to obtain a prepared raw material;
[0135] S03, ball-milling the prepared raw materials to obtain a mixed slurry;
[0136] S04, drying the mixed slurry and pressing to obtain a blank;
[0137] S05. Sintering the blank to obtain a metal-ceramic alloy.
[0138] In the S01:
[0139] In some embodiments, the metal ceramic alloy comprises, by weight percentage:
[0140] Hard phase powder: 30% to 80% first TiCN;
[0141] 1% to 10% second TiCN;
[0142] 0%~5% TiC;
[0143] Binder phase powder: 0% to 10% Ni;
[0144] 0%~10% Co;
[0145] 15%~65% Fe;
[0146] 1.5%~15% W-Fe;
[0147] Carbon-nitrogen balance powder: 0% to 1.5% carbon black;
[0148] The Fsss particle size of the first TiCN powder is greater than the Fsss particle size of the second TiCN powder.
[0149] In the S02:
[0150] In some embodiments, the dispersant comprises dodecylbenzenesulfonic acid, stearic acid, or ethozone.
[0151] In some embodiments, the mass fraction of the dispersant in the total amount of the mixed powder is 0.3% to 0.8%, for example, it can be 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, etc. Within the mass fraction range, the mixed powder can be fully dispersed.
[0152] In some embodiments, the molding agent comprises rubber, wax or PEG.
[0153] In some embodiments, the mass fraction of the forming agent in the total amount of the mixed powder is 2.5% to 8%, for example, it can be 2.5%, 2.8%, 3%, 3.5%, 3.8%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, etc. Within the mass fraction range, the bonding state between the mixed powders is improved, the strength of the pressed green body is ensured, the pressing performance is improved, and the density of the pressed green body is increased.
[0154] In said S03:
[0155] In some embodiments, the prepared raw materials are loaded into a grinding carbide or stainless steel ball mill of a ball mill, and a solvent is added and ball milling is performed to obtain a mixed slurry.
[0156] Further, the solvent includes gasoline, ethylene glycol or hexane.
[0157] Furthermore, the volume mass ratio of the solvent to the mixed powder is 250ml / Kg to 600ml / Kg, for example, it can be 250ml / Kg, 280ml / Kg, 300ml / Kg, 320ml / Kg, 350ml / Kg, 360ml / Kg, 380ml / Kg, 400ml / Kg, 420ml / Kg, 450ml / Kg, 480ml / Kg, 500ml / Kg, 520ml / Kg, 550ml / Kg, 600ml / Kg, etc. Within the volume mass ratio range, it is beneficial to uniformly mix the mixed powder, dispersant, forming agent and solvent.
[0158] Furthermore, the ball mill is a rolling ball mill, and the ball diameter of the cemented carbide ball is 5.5mm-12mm, for example, it can be 5.5mm, 5.8mm, 6mm, 6.25mm, 6.5mm, 6.85mm, 7mm, 7.25mm, 7.5mm, 7.85mm, 8mm, 8.25mm, 8.5mm, 8.75mm, 9mm, 9.25mm, 9.5mm, 9.85mm, 10mm, 10.5mm, 11mm, 11.5mm, 12mm, etc.; the ball-to-material ratio is 3.5-8:1, for example, it can be 3.5:1, 3.8:1, 4:1, 4.2:1, 4.5:1, 4.8: The rotation speed of the ball mill is 38 to 80 rpm, for example, 38 rpm, 40 rpm, 45 rpm, 50 rpm, 55 rpm, 60 rpm, 65 rpm, 70 rpm, 72 rpm, 75 rpm, 76 rpm, 78 rpm, 80 rpm, etc.; the ball milling time is 24h to 80h, for example, 24h, 25h, 30h, 35h, 40h, 45h, 48h, 50h, 55h, 60h, 65h, 70h, 75h, 80h, etc.
[0159] In said S04:
[0160] In some embodiments, the mixed slurry is dried and then passed through an N-mesh filter or spray granulated;
[0161] Furthermore, N mesh is 40 mesh to 120 mesh, for example, it can be 40 mesh, 50 mesh, 60 mesh, 70 mesh, 80 mesh, 90 mesh, 100 mesh, 110 mesh, 120 mesh, etc.
[0162] Furthermore, the powder after filtering or spray granulation is directly loaded into a mold and pressed into a blank.
[0163] Furthermore, the pressing pressure is 150 MPa to 220 MPa, for example, it can be 150 MPa, 160 MPa, 170 MPa, 180 MPa, 190 MPa, 200 MPa, 210 MPa, 220 MPa, etc.
[0164] Furthermore, the holding time is 2 min to 20 min, for example, it can be 2 min, 4 min, 6 min, 8 min, 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, etc.
[0165] In some embodiments, the blank is loaded into a sintering furnace and sequentially enters a heating and degreasing stage, a solid phase sintering stage, and a liquid phase sintering stage. After the liquid phase sintering is completed, the blank enters a furnace cooling stage, and then the metal ceramic alloy is taken out of the furnace.
[0166] Furthermore, the heating and degreasing stage is carried out according to the preheating, vacuuming, heating and insulation procedures, preheating to T1 temperature, insulation time t1; vacuuming to below 10Pa, heating to T2 temperature; heating speed is v1, insulation time t2 at T3 temperature;
[0167] Furthermore, in the solid phase sintering stage, the heating rate does not exceed v2, the heating temperature is increased from T3 to T4, and the temperature is kept for t3; the heating rate does not exceed v3, the heating temperature is increased from T4 to T5, and the temperature is kept for t4; the heating rate does not exceed v4, the heating temperature is increased from T5 to T6, and the temperature is kept for t5; the heating rate does not exceed v5, the heating temperature is increased from T6 to T7, and the temperature is kept for t6;
[0168] Furthermore, when the solid-phase sintering stage is completed and the liquid-phase sintering stage is entered, the temperature is increased to T8 at a heating rate of v6 and maintained for t7, while argon gas with a pressure of P is introduced.
[0169] Furthermore, the T1 is 180°C to 250°C, for example, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, etc.
[0170] The t1 is 60 min to 120 min, for example, it can be 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, etc.
[0171] The T2 is 380°C to 450°C, for example, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, etc.
[0172] The v1 is 3°C / min to 5°C / min, for example, 3°C / min, 3.2°C / min, 3.5°C / min, 3.8°C / min, 4°C / min, 4.2°C / min, 4.5°C / min, 4.8°C / min, 5°C / min, etc.
[0173] The T3 is 450°C to 600°C, for example, it can be 450°C, 450°C, 480°C, 500°C, 520°C, 550°C, 580°C, 600°C, etc.
[0174] The t2 is 60 min to 180 min, for example, it can be 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min, 150 min, 160 min, 170 min, 180 min, etc.
[0175] The v2 does not exceed 10℃ / min, for example, it may be no more than 10℃ / min, no more than 9.8℃ / min, no more than 9.5℃ / min, no more than 9.2℃ / min, no more than 9℃ / min, no more than 8.5℃ / min, no more than 8℃ / min, no more than 7.5℃ / min, no more than 7℃ / min, no more than 6.5℃ / min, no more than 6℃ / min, no more than 5.5℃ / min, no more than 5℃ / min, etc.
[0176] The T4 is 750°C to 850°C, for example, 750°C, 760°C, 780°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, etc.
[0177] The t3 is 60 min to 180 min, for example, it can be 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min, 150 min, 160 min, 170 min, 180 min, etc.
[0178] The v3 does not exceed 10℃ / min, for example, it may be no more than 10℃ / min, no more than 9.8℃ / min, no more than 9.5℃ / min, no more than 9.2℃ / min, no more than 9℃ / min, no more than 8.5℃ / min, no more than 8℃ / min, no more than 7.5℃ / min, no more than 7℃ / min, no more than 6.5℃ / min, no more than 6℃ / min, no more than 5.5℃ / min, no more than 5℃ / min, etc.
[0179] The T5 is 1000°C to 1100°C, for example, it can be 1000°C, 1010°C, 1020°C, 1030°C, 1040°C, 1050°C, 1060°C, 1070°C, 1080°C, 1090°C, 1100°C, etc.
[0180] The t4 is 60 min to 180 min, for example, it can be 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min, 150 min, 160 min, 170 min, 180 min, etc.
[0181] The v4 does not exceed 10℃ / min, for example, it may be no more than 10℃ / min, no more than 9.8℃ / min, no more than 9.5℃ / min, no more than 9.2℃ / min, no more than 9℃ / min, no more than 8.5℃ / min, no more than 8℃ / min, no more than 7.5℃ / min, no more than 7℃ / min, no more than 6.5℃ / min, no more than 6℃ / min, no more than 5.5℃ / min, no more than 5℃ / min, etc.
[0182] The T6 is 1200°C to 1250°C, for example, it can be 1200°C, 1210°C, 1220°C, 1230°C, 1240°C, 1250°C, etc.
[0183] The t5 is 120 min to 300 min, for example, it can be 120 min, 150 min, 180 min, 200 min, 220 min, 250 min, 260 min, 280 min, 300 min, etc.
[0184] The v5 does not exceed 5°C / min, for example, it may be no more than 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, etc.
[0185] The T7 is 1300°C to 1350°C, for example, 1300°C, 1310°C, 1320°C, 1330°C, 1340°C, 1350°C, etc.
[0186] The t6 is 60 min to 120 min, for example, it can be 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, or 120 min.
[0187] The v6 does not exceed 5°C / min, for example, it may be no more than 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, etc.
[0188] The T8 is 1350°C to 1500°C, for example, it can be 1350°C, 1380°C, 1400°C, 1420°C, 1450°C, 1480°C, 1500°C, etc.
[0189] The t7 is 60 min to 300 min, for example, it can be 60 min, 80 min, 100 min, 120 min, 150 min, 180 min, 200 min, 220 min, 250 min, 280 min, 300 min, etc.
[0190] The P is 1 MPa to 5 MPa, for example, 1 MPa, 1.5 MPa, 2 MPa, 2.5 MPa, 3 MPa, 3.5 MPa, 4 MPa, 4.5 MPa, 5 MPa, etc.
[0191] The purity of the argon gas is greater than 99.995%.
[0192] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.
[0193] Example 1
[0194] See also Figure 2 , a micro-nano twin-crystal plate-like structure titanium carbonitride-based metal ceramic alloy, wherein the metal ceramic alloy comprises, by mass percentage: 50% first TiCN; 7% second TiCN; 2.5% TiC; 5% Ni; 5% Co; 20% Fe; 10% W-Fe; 0.5% carbon black;
[0195] The first TiCN powder Fsss has a particle size of 3 microns;
[0196] The second TiCN powder Fsss has a particle size of 0.5 μm;
[0197] The particle size of TiC powder Fsss is 2.0 μm;
[0198] The particle size of Ni powder Fsss is 1.2 μm;
[0199] The particle size of Co powder Fsss is 1.0 μm;
[0200] The particle size of Fe powder Fsss is 15 μm;
[0201] The particle size of W-Fe powder Fsss is 18 μm;
[0202] The particle size of carbon black powder Fsss is 0.4 μm;
[0203] Fe powder is carbonyl iron powder;
[0204] The mass percentage of W in W-Fe is 60%;
[0205] A method for preparing a micro-nano twin-crystal plate-like structure titanium carbonitride-based metal ceramic alloy comprises:
[0206] Step 1, weighing hard phase powder, binder phase powder and carbon-nitrogen balance powder according to the above mass percentage and mixing them to obtain a mixed powder, adding a dispersant and a molding agent, and mixing them evenly to obtain a prepared raw material; the dispersant is dodecylbenzenesulfonic acid, and its mass fraction of the total amount of the mixed powder is 0.5%; the molding agent is paraffin, and its mass fraction of the total amount of the mixed powder is 5.5%;
[0207] Step 2, the prepared raw materials are loaded into the grinding carbide ball mill of the rolling ball mill, and a solvent is added and ball milled to obtain a mixed slurry, wherein the solvent is ethylene glycol, the volume mass ratio of ethylene glycol to the total amount of the mixed powder is 420 ml / kg, the ball diameter of the carbide ball is 8.5 mm, and the ball-to-material ratio is 6:1; the ball milling speed of the ball mill is 60 rpm, and the ball milling time is 52 h;
[0208] Step 3, drying the mixed slurry (75°C, 1.8h) and filtering through 80 mesh;
[0209] Step 4: directly put the powder after filtering into the mold and press it into a blank. The pressing pressure is 185Mpa and the holding time is 12min.
[0210] Step 5, loading the blank into the sintering furnace and sequentially entering the heating and degreasing stage, the solid phase sintering stage, and the liquid phase sintering stage. After the liquid phase sintering is completed, it enters the furnace cooling stage, and then the metal ceramic alloy is taken out of the furnace. Among them, the heating and degreasing stage is carried out according to the preheating, vacuuming, heating and insulation processes, preheating to 215°C, and insulation time for 90 minutes; vacuuming to below 10Pa, heating to 415°C; heating rate is 4°C / min, and insulation time is 120 minutes at 525°C; in the solid phase sintering stage, the heating rate does not exceed 9°C / min, the heating temperature is increased from 525°C to 800°C, and insulation time is 120 minutes ; The heating rate does not exceed 9.5℃ / min, the heating temperature is increased from 800℃ to 1050℃, and the temperature is kept for 120min; the heating rate does not exceed 9℃ / min, the heating temperature is increased from 1050℃ to 1225℃, and the temperature is kept for 210min; the heating rate does not exceed 4℃ / min, the heating temperature is increased from 1225℃ to 1325℃, and the temperature is kept for 90min; after the solid-phase sintering stage is completed and the liquid-phase sintering stage is entered, the temperature is increased to 1425℃ at a heating rate of 3℃ / min, and the temperature is kept for 180min, and argon gas with a pressure of 3MPa is introduced at the same time, and the purity of the argon gas is greater than 99.995%.
[0211] Example 2
[0212] See also Figure 3 , a micro-nano twin-crystal plate-like structure titanium carbonitride-based metal ceramic alloy, wherein the metal ceramic alloy comprises, by mass percentage: 30% first TiCN; 3% second TiCN; 1% TiC; 6% Ni; 4% Co; 45% Fe; 10% W-Fe; 1% carbon black;
[0213] The first TiCN powder Fsss has a particle size of 5 microns;
[0214] The second TiCN powder Fsss has a particle size of 0.7 microns;
[0215] The particle size of TiC powder Fsss is 1.0 μm;
[0216] The particle size of Ni powder Fsss is 1.5 μm;
[0217] The particle size of Co powder Fsss is 1.2 μm;
[0218] The particle size of Fe powder Fsss is 10 μm;
[0219] The particle size of W-Fe powder Fsss is 15 μm;
[0220] The particle size of carbon black powder Fsss is 0.3 μm;
[0221] Fe powder is carbonyl iron powder;
[0222] The mass percentage of W in W-Fe is 50%;
[0223] The preparation method of the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy is the same as that of Example 1.
[0224] Example 3
[0225] See also Figure 4 , a micro-nano twin-crystal plate-like structure titanium carbonitride-based metal ceramic alloy, wherein the metal ceramic alloy comprises, by mass percentage: 64% first TiCN; 10% second TiCN; 3% TiC; 2% Ni; 2% Co; 15% Fe; 3% W-Fe; 1% carbon black;
[0226] The first TiCN powder Fsss has a particle size of 2 microns;
[0227] The second TiCN powder Fsss has a particle size of 0.1 μm;
[0228] The particle size of TiC powder Fsss is 1.2 μm;
[0229] The particle size of Ni powder Fsss is 1 μm;
[0230] The particle size of Co powder Fsss is 0.8 μm;
[0231] The particle size of Fe powder Fsss is 10 μm;
[0232] The particle size of W-Fe powder Fsss is 12 μm;
[0233] The particle size of carbon black powder Fsss is 0.1 μm;
[0234] Fe powder is reduced iron powder;
[0235] The mass percentage of W in W-Fe is 70%;
[0236] The preparation method of the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy is the same as that of Example 1.
[0237] Example 4
[0238] See also Figure 5 , a micro-nano twin-crystal plate-like structure titanium carbonitride-based metal ceramic alloy, wherein the metal ceramic alloy comprises, by mass percentage: 70% first TiCN; 10% second TiCN; 1.5% TiC; 1% Ni; 1% Co; 14% Fe; 2% W-Fe; 0.5% carbon black;
[0239] The first TiCN powder Fsss has a particle size of 6 microns;
[0240] The second TiCN powder Fsss has a particle size of 0.8 μm;
[0241] TiC powder Fsss particle size is 3.0 μm;
[0242] The particle size of Ni powder Fsss is 2 μm;
[0243] The particle size of Co powder Fsss is 2 μm;
[0244] The particle size of Fe powder Fsss is 18 μm;
[0245] The particle size of W-Fe powder Fsss is 20 μm;
[0246] The particle size of carbon black powder Fsss is 0.8 μm;
[0247] Fe powder is carbonyl iron powder;
[0248] The mass percentage of W in W-Fe is 55%;
[0249] The preparation method of the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy is the same as that of Example 1.
[0250] Example 5
[0251] See also Figure 6 , a micro-nano twin-crystal plate-like structure titanium carbonitride-based metal ceramic alloy, wherein the metal ceramic alloy comprises, by mass percentage: 46% first TiCN; 1% second TiCN; 1.2% TiC; 8% Ni; 8% Co; 24% Fe; 11% W-Fe; 0.8% carbon black;
[0252] The first TiCN powder Fsss has a particle size of 1.9 microns;
[0253] The second TiCN powder Fsss has a particle size of 0.6 microns;
[0254] The particle size of TiC powder Fsss is 1.5 μm;
[0255] The particle size of Ni powder Fsss is 1.0 μm;
[0256] The particle size of Co powder Fsss is 1.0 μm;
[0257] The particle size of Fe powder Fsss is 20 μm;
[0258] The particle size of W-Fe powder Fsss is 20 μm;
[0259] The particle size of carbon black powder Fsss is 0.5 μm;
[0260] Fe powder is carbonyl iron powder;
[0261] The mass percentage of W in W-Fe is 48%;
[0262] The preparation method of the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy is the same as that of Example 1.
[0263] Example 6
[0264] See also Figure 7 , a micro-nano twin-crystal plate-like structure titanium carbonitride-based metal ceramic alloy, wherein the metal ceramic alloy comprises, by mass percentage: 36% first TiCN; 6% second TiCN; 1.5% TiC; 5% Ni; 8% Co; 27% Fe; 15% W-Fe; 1.5% carbon black;
[0265] The first TiCN powder Fsss has a particle size of 4 microns;
[0266] The second TiCN powder Fsss has a particle size of 0.7 microns;
[0267] The particle size of TiC powder Fsss is 1.8 μm;
[0268] The particle size of Ni powder Fsss is 2 μm;
[0269] The particle size of Co powder Fsss is 1.5 μm;
[0270] The particle size of Fe powder Fsss is 28 μm;
[0271] The particle size of W-Fe powder Fsss is 30 μm;
[0272] The particle size of carbon black powder Fsss is 0.6 μm;
[0273] Fe powder is carbonyl iron powder;
[0274] The mass percentage of W in W-Fe is 65%;
[0275] The preparation method of the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy is the same as that of Example 1.
[0276] Example 7
[0277] See also Figure 8 , a micro-nano twin-crystal plate-like structure titanium carbonitride-based metal ceramic alloy, wherein the metal ceramic alloy comprises, by mass percentage: 62% first TiCN; 5% second TiCN; 4.5% TiC; 5% Ni; 3% Co; 18% Fe; 2% W-Fe; 0.5% carbon black;
[0278] The first TiCN powder Fsss has a particle size of 5 microns;
[0279] The second TiCN powder Fsss has a particle size of 0.9 μm;
[0280] The particle size of TiC powder Fsss is 2.5 μm;
[0281] The particle size of Ni powder Fsss is 2 μm;
[0282] The particle size of Co powder Fsss is 2.2 μm;
[0283] The particle size of Fe powder Fsss is 20 μm;
[0284] The particle size of W-Fe powder Fsss is 28 μm;
[0285] The particle size of carbon black powder Fsss is 0.2 μm;
[0286] Fe powder is carbonyl iron powder;
[0287] The mass percentage of W in W-Fe is 75%;
[0288] The preparation method of the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy is the same as that of Example 1.
[0289] Example 8
[0290] A micro-nano twin-crystal plate-like structure titanium carbonitride-based metal-ceramic alloy, wherein the metal-ceramic alloy comprises, by mass percentage: 47% first TiCN; 8% second TiCN; 35% Fe; 10% W-Fe;
[0291] The first TiCN powder Fsss has a particle size of 4 microns;
[0292] The second TiCN powder Fsss has a particle size of 0.6 microns;
[0293] The particle size of Fe powder Fsss is 50 μm;
[0294] The particle size of W-Fe powder Fsss is 58 μm;
[0295] Fe powder is carbonyl iron powder;
[0296] The mass percentage of W in W-Fe is 75%;
[0297] The preparation method of the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy is the same as that of Example 1.
[0298] Example 9
[0299] A micro-nano twin-crystal plate-shaped titanium carbonitride-based metal-ceramic alloy, wherein the metal-ceramic alloy comprises, by mass percentage: 30% first TiCN; 10% second TiCN; 45% Fe; 15% W-Fe;
[0300] The first TiCN powder Fsss has a particle size of 3 microns;
[0301] The second TiCN powder Fsss has a particle size of 0.4 μm;
[0302] The particle size of Fe powder Fsss is 30 μm;
[0303] The particle size of W-Fe powder Fsss is 28 μm;
[0304] Fe powder is reduced iron powder;
[0305] The mass percentage of W in W-Fe is 66%;
[0306] The preparation method of the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy is the same as that of Example 1.
[0307] Example 10
[0308] A micro-nano twin-crystal plate-like structure titanium carbonitride-based metal-ceramic alloy, wherein the metal-ceramic alloy comprises, by mass percentage: 80% first TiCN; 3.5% second TiCN; 15% Fe; 1.5% W-Fe;
[0309] The first TiCN powder Fsss has a particle size of 2 microns;
[0310] The second TiCN powder Fsss has a particle size of 0.4 μm;
[0311] The particle size of Fe powder Fsss is 60 μm;
[0312] The particle size of W-Fe powder Fsss is 55 μm;
[0313] Fe powder is carbonyl iron powder;
[0314] The mass percentage of W in W-Fe is 50%;
[0315] The preparation method of the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy is the same as that of Example 1.
[0316] Embodiment 11
[0317] The difference between this embodiment and embodiment 1 is that:
[0318] A method for preparing a micro-nano twin-crystal plate-like structure titanium carbonitride-based metal ceramic alloy comprises:
[0319] Step 1, weighing hard phase powder, binder phase powder and carbon-nitrogen balance powder according to the above mass percentage and mixing them to obtain a mixed powder, adding a dispersant and a molding agent, and mixing them evenly to obtain a prepared raw material; the dispersant is stearic acid, and its mass fraction of the total amount of the mixed powder is 0.3%; the molding agent is PEG, and its mass fraction of the total amount of the mixed powder is 2.5%;
[0320] Step 2, loading the prepared raw materials into the grinding carbide ball mill of the rolling ball mill, adding a solvent and performing ball milling to obtain a mixed slurry, wherein the solvent is gasoline, the volume mass ratio of gasoline to the total amount of the mixed powder is 250 ml / kg, the ball diameter of the carbide ball is 5.5 mm, and the ball-to-material ratio is 3.5:1; the ball milling speed of the ball mill is 38 rpm, and the ball milling time is 80 h;
[0321] Step 3, drying the mixed slurry (85°C, 1.5h) and filtering through 120 mesh;
[0322] Step 4: directly put the powder after filtering into the mold and press it into a blank. The pressing pressure is 150 MPa and the holding time is 20 minutes.
[0323] Step 5, loading the blank into the sintering furnace and sequentially entering the heating and degreasing stage, the solid phase sintering stage, and the liquid phase sintering stage, entering the furnace cooling stage after the liquid phase sintering is completed, and then taking out the metal ceramic alloy from the furnace, wherein the heating and degreasing stage is carried out according to the preheating, vacuuming, heating and insulation procedures, preheating to 180°C, and insulation time for 120min; vacuuming to below 10Pa, heating to 380°C; heating rate of 3°C / min, insulation time at 450°C for 180min; in the solid phase sintering stage, the heating rate does not exceed 6°C / min, the heating temperature is increased from 450°C to 750°C, and insulation time for 180min; The heating rate does not exceed 6.5°C / min, the heating temperature is increased from 750°C to 1000°C, and the temperature is kept for 180 minutes; the heating rate does not exceed 7.0°C / min, the heating temperature is increased from 1000°C to 1200°C, and the temperature is kept for 300 minutes; the heating rate does not exceed 2°C / min, the heating temperature is increased from 1200°C to 1300°C, and the temperature is kept for 120 minutes; after the solid-phase sintering stage is completed and the liquid-phase sintering stage is entered, the temperature is increased to 1350°C at a heating rate of 2°C / min, and the temperature is kept for 300 minutes, and argon gas with a pressure of 1MPa is introduced at the same time, and the purity of the argon gas is greater than 99.995%.
[0324] The rest is the same as in Example 1.
[0325] Example 12
[0326] The difference between this embodiment and embodiment 1 is that:
[0327] A method for preparing a micro-nano twin-crystal plate-like structure titanium carbonitride-based metal ceramic alloy comprises:
[0328] Step 1, weighing hard phase powder, binder phase powder and carbon-nitrogen balance powder according to the above mass percentage and mixing them to obtain a mixed powder, adding a dispersant and a molding agent, and mixing them evenly to obtain a prepared raw material; the dispersant is ethisomin, and its mass fraction of the total amount of the mixed powder is 0.8%; the molding agent is rubber, and its mass fraction of the total amount of the mixed powder is 8%;
[0329] Step 2, loading the prepared raw materials into the grinding carbide ball mill of the rolling ball mill, adding a solvent and performing ball milling to obtain a mixed slurry, wherein the solvent is hexane, the volume mass ratio of hexane to the total amount of the mixed powder is 600 ml / kg, the ball diameter of the carbide ball is 12 mm, and the ball-to-material ratio is 8:1; the ball milling speed of the ball mill is 80 rpm, and the ball milling time is 24 h;
[0330] Step 3, drying the mixed slurry (72°C, 2.2h) and filtering through 40 mesh;
[0331] Step 4: directly put the powder after filtering into the mold and press it into a blank. The pressing pressure is 220 MPa and the holding time is 2 min.
[0332] Step 5, loading the blank into the sintering furnace and sequentially entering the heating and degreasing stage, the solid phase sintering stage, and the liquid phase sintering stage, entering the furnace cooling stage after the liquid phase sintering, and then taking out the metal ceramic alloy from the furnace, wherein the heating and degreasing stage is carried out according to the preheating, vacuuming, heating and insulation procedures, preheating to 250°C, and insulation time for 60 minutes; vacuuming to below 10Pa, heating to 450°C; heating rate is 5°C / min, and insulation time is 60 minutes at 600°C; in the solid phase sintering stage, the heating rate does not exceed 9.8°C, the heating temperature is increased from 600°C to 850°C, and insulation time is 60 minutes; heating The heating rate does not exceed 9.5℃ / min, the heating temperature is increased from 850℃ to 1100℃, and the temperature is kept for 60min; the heating rate does not exceed 9.2℃ / min, the heating temperature is increased from 1100℃ to 1250℃, and the temperature is kept for 120min; the heating rate does not exceed 5℃ / min, the heating temperature is increased from 1250℃ to 1350℃, and the temperature is kept for 60min; after the solid-phase sintering stage is completed and the liquid-phase sintering stage is entered, the temperature is increased to 1500℃ at a heating rate of 5℃ / min, and the temperature is kept for 60min, and argon gas with a pressure of 5MPa is introduced at the same time, and the purity of the argon gas is greater than 99.995%.
[0333] The rest is the same as in Example 1.
[0334] Comparative Example 1
[0335] Commercially available conventional MT52 alloy.
[0336] The properties of the titanium carbonitride-based metal ceramic alloy with a micro-nano twinned plate-like structure obtained in each embodiment of the present invention were verified, and the comparative example was a traditional MT52 alloy. The test results are shown in Table 1.
[0337] Table 1 Performance comparison between micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy and traditional MT52 alloy
[0338]
[0339]
[0340] As can be seen from Table 1, compared with the traditional MT52 alloy, the hardness, bending strength and fracture toughness of the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy prepared by the present invention are significantly improved.
[0341] The above is a detailed introduction to the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy and its preparation method provided in the embodiments of the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for technical personnel in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. Micro-nano twin-crystal plate-like structure titanium carbonitride-based metal ceramic alloy, characterized by: Measured by mass percentage, the metal ceramic alloy comprises: Hard phase powder: 30% to 80% first TiCN; 1% to 10% second TiCN; 0%~5%TiC; Binder phase powder: 0% to 10% Ni; 0%~10%Co; 15%~65%Fe; 1.5%~15%W-Fe; Carbon-nitrogen balance powder: 0% to 1.5% carbon black; The Fsss particle size of the first TiCN powder is greater than the Fsss particle size of the second TiCN powder.
2. The micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy according to claim 1, characterized in that: Measured by mass percentage, the metal ceramic alloy comprises: Hard phase powder: 30% to 80% first TiCN; 1% to 10% second TiCN; 0.1%~5%TiC; Binder phase powder: 0.1% to 10% Ni; 0.1%~10%Co; 15%~65%Fe; 1.5%~15%W-Fe; Carbon-nitrogen balance powder: 0.1% to 1.5% carbon black.
3. The micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy according to claim 1 or 2, characterized in that: The first TiCN powder Fsss has a particle size greater than 1.8 μm and less than 6.5 μm; and / or The second TiCN powder Fsss has a particle size of less than 1.0 μm; and / or TiC powder Fsss particle size not greater than 3.5 microns; and / or Ni powder Fsss particle size is not greater than 3.0 microns; and / or Co powder Fsss particle size is not greater than 3.0 microns; and / or The particle size of Fe powder Fsss is not greater than 100.0 microns; and / or The particle size of the W-Fe powder Fsss is not greater than 100.0 microns; and / or The particle size of the carbon black powder Fsss is less than 1.0 micron.
4. The micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy according to claim 1 or 2, characterized in that: The Fe powder is carbonyl iron powder or reduced iron powder; and / or The mass percentage of W in W-Fe is 45% to 85%.
5. A method for preparing a micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy, characterized in that: The preparation method comprises: Providing a mixed powder, the mixed powder comprising the hard phase powder, the binder phase powder and the carbon-nitrogen balance powder in the above-mentioned mass percentages; Adding a dispersant and a molding agent to the mixed powder and mixing them evenly to obtain a prepared raw material; ball-milling the prepared raw materials to obtain a mixed slurry; Drying the mixed slurry and pressing to obtain a blank; The blank is sintered to obtain a metal-ceramic alloy.
6. The method for preparing the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy according to claim 5, characterized in that: The prepared raw materials are placed in a grinding carbide or stainless steel ball mill of a ball mill, and a solvent is added and ball milled to obtain a mixed slurry; and / or The mixed slurry is dried and passed through an N-mesh filter or spray granulated. The powder after the filter or spray granulation is directly loaded into a mold and pressed into a blank.
7. The method for preparing the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy according to claim 6, characterized in that: The dispersant comprises dodecylbenzenesulfonic acid, stearic acid or ethozone; and / or The molding agent comprises rubber, paraffin or PEG; and / or Solvents include gasoline, ethylene glycol, or hexane.
8. The method for preparing the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy according to claim 6, characterized in that: The mass fraction of the dispersant in the total amount of the mixed powder is 0.3% to 0.8%; and / or The mass fraction of the molding agent in the total amount of the mixed powder is 2.5% to 8%; and / or The volume mass ratio of the solvent to the mixed powder is 250ml / Kg to 600ml / Kg; and / or The ball mill is a rolling ball mill, the diameter of the carbide balls is 5.5 mm to 12 mm, the ball-to-material ratio is 3.5 to 8:1, the speed of the ball mill is 38 rpm to 80 rpm, and the ball milling time is 24 h to 80 h; and / or N mesh is 40 mesh to 120 mesh; and / or The pressing pressure is 150Mpa to 220Mpa; and / or The pressure holding time is 2min to 20min.
9. The method for preparing the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy according to claim 5, characterized in that: The blank is loaded into the sintering furnace and enters the heating and degreasing stage, the solid phase sintering stage, and the liquid phase sintering stage in sequence. After the liquid phase sintering is completed, it enters the furnace cooling stage, and then the metal ceramic alloy is taken out of the furnace; The heating and degreasing stage is carried out according to the preheating, vacuuming, heating and insulation procedures, preheating to T1 temperature, insulation time t1; vacuuming to below 10Pa, heating to T2 temperature; heating speed is v1, insulation time t2 at T3 temperature; During the solid phase sintering stage, the heating rate does not exceed v2, the heating temperature is increased from T3 to T4, and the temperature is kept for t3; the heating rate does not exceed v3, the heating temperature is increased from T4 to T5, and the temperature is kept for t4; the heating rate does not exceed v4, the heating temperature is increased from T5 to T6, and the temperature is kept for t5; the heating rate does not exceed v5, the heating temperature is increased from T6 to T7, and the temperature is kept for t6; After the solid phase sintering stage is completed and the liquid phase sintering stage is entered, the temperature is increased to T8 at a heating rate of v6 and maintained at t7, while argon gas with a pressure of P is introduced.
10. The method for preparing the micro-nano twinned plate-like structure titanium carbonitride-based metal ceramic alloy according to claim 9, characterized in that: T1 is 180°C to 250°C; and / or t1 is 60 min to 120 min; and / or T2 is 380°C to 450°C; and / or v1 is 3℃ / min~5℃ / min; and / or T3 is 450°C to 600°C; and / or t2 is 60 min to 180 min; and / or v2 does not exceed 10℃ / min; and / or T4 is 750℃~850℃; and / or t3 is 60min~180min; and / or v3 does not exceed 10℃ / min; and / or T5 is 1000℃~1100℃; and / or t4 is 60min~180min; and / or v4 does not exceed 10℃ / min; and / or T6 is 1200℃~1250℃; and / or t5 is 120min~300min; and / or v5 does not exceed 5℃ / min; and / or T7 is 1300℃~1350℃; and / or t6 is 60min~120min; and / or v6 does not exceed 5℃ / min; and / or T8 is 1350℃~1500℃; and / or t7 is 60min~300min; and / or P is 1MPa~5MPa.
Citation Information
Cited By
High-entropy light hard alloy cement high-pressure roller mill stud nail, preparation method thereof and high-pressure roller mill
CN121610695A
A high-entropy cemented carbide stud for high-pressure roller mills and a method for producing the same, and a high-pressure roller mill
CN121610695B